أثر تغير متوسـط نصيب الفرد من الإنفاق الاسـتهلاكي الخاص على التنمية الاقتصاديـة في سـوريـة دراسـة تحليليـة بين عامي 2000و 2010 - أحـمد طـالب; أطـوز ملك (Latakia University Journal - Economic and Legal Sciences Series, 2015)
يعبر متوسـط نصيب الفرد من الإنفاق الاسـتهلاكي الخاص ونسـبته من الناتج المحلي الإجمالي عن مسـتوى معيشـة الفرد في المجتمع. لذلك يهدف هـذا البحـث إلى الوصول لأثر التغيرات الحاصلـة في متوسـط نصيب الفرد السـنوي من الإنفاق الاسـتهلاكي الخاص على التنميـة الاقتصاديـة في سـوريـة، من خلال تحليل تأثير بعض مؤشـرات التنميـة الاقتصاديـة على الناتج المحلي الإجمالي وذلك باسـتخدام أسـلوب الانحدار المتدرج Stepwise Regression بالادخال التدريجي للمتغيرات المسـتقلة وهي الإنفاق الاسـتهلاكي الخاص والادخار والاسـتثمار والقروض والواردات الاسـتهلاكيـة، للوصول إلى نموذج انحدار يعبر عن تأثيرها على الناتج المحلي الإجمالي. ومن ثم تحليل تأثير التغيرات الحاصلة في متوسـط نصيب الفرد السـنوي من الإنفاق الاسـتهلاكي الخاص على متوسـط نصيبـه من الادخار والاسـتثمار والقروض والواردات الاسـتهلاكيـة، وذلك باسـتخدام أسـلوب Curve estimation للوصول إلى أفضل نموذج يعبر عن العلاقـة بين متغيرات البحـث. وتوصل البحـث إلى مجموعـة من النتائج تتلخص في أنـه يرتفع متوسـط نصيب الفرد السـنوي من الناتج المحلي الإجمالي كلما ارتفع متوسـط نصيبه من الإنفاق الاسـتهلاكي الخاص، ويؤدي ارتفاع متوسـط نصيب الفرد السـنوي من الإنفاق الاسـتهلاكي الخاص إلى انخفاض متوسـط نصيبـه من الادخـار، وبالمقابل يؤدي إلى ارتفاع متوسـط نصيبـه من الاسـتثمار، القروض، والواردات الاسـتهلاكيـة خلال فترة البحـث. The average per capita of private expenditure and its rate of GDP is reflecting the standard of individual living in the society. Therefore, this research aim to identify the impact of changing average per capita of private expenditure on economic development in Syria, through analysing impact of some important economic development indicators on GDP, by applying stepwise regression method, and entering independent variables which are, private expenditure, saving, investment, loans, and consuming imports to reach the regression model expresses impact on GDP. Then, analysing impacts of annual changing average per capita of private expenditure on per capita on saving, investment, loans, and consuming imports. By using Curve Estimation method to reach the best model expresses the relation between variables of research. The research found a set of results are summarized that, the annual per capita of GDP is increasing, with an increase in annual per capita of private expenditure, also the increase of annual per capita of private expenditure led to decrease the annual average per capita of saving, and led to increase the annual average per capita of investment, loan, and consuming imports during the research period.